Analysis and design of optimal demultiplexer based on Mach-Zehnder interferometer for CWDM application - Cholan, Noran Azizan (IEEE, 2008)
Optimal design of planar circuit demultiplexer based on Mach-Zehnder interferometers and their cascaded forms are presented. A demultiplexer is designed for each two and four channels (wavelengths) respectively for Coarse Wavelength Division Multiplexing (CWDM) application which follows ITU-T G.694.2 standard. Optimized demultiplexer should have high transmission to get high power efficiency and low cross talk to avoid signal degradation. An analytical equation is presented to calculate the length difference (?L) between the two arms of a Mach-Zehnder interferometer to produce different phase shift. Based on the length difference (.?L) calculation, Mach-Zehnder interferometer for different wavelengths is designed. Directional coupler is analyzed in such a way that it can split the power equally. Coupled Mode Theory (CMT) and Beam Propagation Method (BPM) is used as an analytical and numerical method respectively. Performance comparisons in terms of transmission, cross talk and 3 dB bandwidth are implemented for the demultiplexer. Transmission (dB) as high as -0.74 dB and cross talk as low as -21.06 dB have been obtained for four channel demultiplexer at wavelength, ? = 1470nm. A 3 dB bandwidth of 14nm has been recorded as well, which satisfies the requirement set by ITU-T G.694.2 which is 20 nm. Qualitative agreement between Beam Propagation Method (BPM) and calculation based on Coupled Mode Theory (CMT) has been achieved for each two and four channels demultiplexer respectively.